Middlemarch - Eliot, George, 1819-1880 (Dover thrift editions, 2015)
"Praised by Virginia Woolf as "one of the few English novels written for grown-up people," Middlemarch offers remarkably modern psychological insights. George Eliot's splendidly plotted tale unfolds in an English town of the 1830s, where memorable residents include an idealistic young woman, an ambitious doctor, and a financier with a secret past"--